2013
DOI: 10.5830/cvja-2013-035
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of hypertension and factors associated with uncontrolled hypertension in Sudanese adults : cardiovascular topic

Abstract: BackgroundThe incidence of hypertension (HTN) has increased rapidly in the Sudan in the last few years. The aim of this study was to determine the prevalence of uncontrolled HTN and the risk factors associated with it in Sudanese adults.MethodsThis study was cross sectional. Data were collected using structured questionnaires filled in during interviews with subjects visiting referral clinics in Khartoum, the capital city of Sudan. Blood pressure (BP) was measured using a digital sphygmomanometer. A digital ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
35
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 32 publications
10
35
2
2
Order By: Relevance
“…Level of education was significantly associated with hypertension complications p=0.001,this is in line with a study done in Sudan, where uncontrolled blood pressure among 25% of subjects were illiterate, lack of BP control increased with increase in educational level [16].…”
Section: Discussionsupporting
confidence: 89%
“…Level of education was significantly associated with hypertension complications p=0.001,this is in line with a study done in Sudan, where uncontrolled blood pressure among 25% of subjects were illiterate, lack of BP control increased with increase in educational level [16].…”
Section: Discussionsupporting
confidence: 89%
“…14,15 Within sociodemographic and socioeconomic factors, only gender showed a significant association with uncontrolled hypertension in the study. Other studies that showed a significant association between male gender and uncontrolled hypertension as re- 9,[16][17][18] The possible reason among female gender with better control on hypertension is proved due to the protective and regulatory effect of the hormone estrogen. In addition, males were reported to be less likely to seek medical attention compared to females in case of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, males were reported to be less likely to seek medical attention compared to females in case of hypertension. 17 Their lack of time to adopt a healthy lifestyle, enjoyment to be among fellow smokers and men's perception of invulnerability to illness also contributed towards the problem. 9 This study suggests the importance of raising hypertension awareness as well as controlling hypertension in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was significant association of age (p-value = 0.001), social status (p-value = 0.001), stress (p-value = 0.010), and diabetes (p-value = 0.050) with hypertension. The present study has highlighted the significant factors associated with hypertension that encourages the public health professionals to carry out awareness and prevention programs.A study conducted by Babiker et al (2013) used structured questionnaires to investigate the awareness and factors linked with the uncontrolled hypertension among the Sudanese adults. The results showed that prevalence of…”
mentioning
confidence: 99%